2012
DOI: 10.3390/v4030414
|View full text |Cite
|
Sign up to set email alerts
|

Folding and Oligomerization of the gp2b/gp3/gp4 Spike Proteins of Equine Arteritis Virus in Vitro

Abstract: Equine arteritis virus (EAV) is a small, positive-stranded RNA virus. The glycoproteins gp2b, gp3 and gp4 form a heterotrimer in the viral envelope, which is required for cell entry of EAV. We describe expression of the ectodomains of the proteins in E. coli and their refolding from inclusion bodies. After extraction of inclusion bodies and dialysis, Gst-, but not His-tagged proteins, refold into a soluble conformation. However, when dialyzed together with Gst-gp3 or with Gst-gp4, His-gp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Similarly, the cysteine residue of GP4 that interacts with Cys-102 of GP2 has not been identified. It has been shown that folding and oligomerization of GP2, GP3, and GP4 expressed in E. coli are independent processes (Kabatek, 2013). However, it remains to be shown whether this is true in virus-infected cells.…”
Section: Gp2/gp3/gp4 Heterotrimeric Complexmentioning
confidence: 99%
“…Similarly, the cysteine residue of GP4 that interacts with Cys-102 of GP2 has not been identified. It has been shown that folding and oligomerization of GP2, GP3, and GP4 expressed in E. coli are independent processes (Kabatek, 2013). However, it remains to be shown whether this is true in virus-infected cells.…”
Section: Gp2/gp3/gp4 Heterotrimeric Complexmentioning
confidence: 99%
“…Since two cysteine residues must be in very close vicinity to form a covalent bond, Gp3 is likely to be non-covalently associated with the Gp2/4 dimer already in budding virus particles (Wieringa et al, 2003b). Accordingly, the minor glycoproteins can associate with each other independently of glycosylation and disulphide bonds, as demonstrated by refolding experiments with the ectodomains of these proteins purified from E. coli (Kabatek and Veit, 2012).…”
Section: Disulphide Linkage Of Gp3 With Gp2/gp4mentioning
confidence: 99%
“…This is followed by association of both proteins and stabilization of the resulting dimer by an intermolecular disulphide bond (Wieringa et al, 2003a). Since Gp3 is capable to associate with Gp2/4 in virus particles and also with Gp2 and Gp4 in vitro (Kabatek and Veit, 2012), the question arises what prevents formation of the Gp2/3/4 trimer already in the ER and what triggers its build-up later on. One might speculate that a conformational rearrangement occurs in Gp2/4 and Gp3 after transport from the ER to the Golgi, which might be triggered by the different milieu present in the Golgi lumen.…”
Section: Building the Gp2/3/4 Spikementioning
confidence: 99%
See 1 more Smart Citation